2016
DOI: 10.1038/ncomms11112
|View full text |Cite
|
Sign up to set email alerts
|

Individual heritable differences result in unique cell lymphocyte receptor repertoires of naïve and antigen-experienced cells

Abstract: The adaptive immune system's capability to protect the body requires a highly diverse lymphocyte antigen receptor repertoire. However, the influence of individual genetic and epigenetic differences on these repertoires is not typically measured. By leveraging the unique characteristics of B, CD4+ T and CD8+ T-lymphocyte subsets from monozygotic twins, we quantify the impact of heritable factors on both the V(D)J recombination process and on thymic selection. We show that the resulting biases in both V(D)J usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
161
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(180 citation statements)
references
References 36 publications
17
161
1
Order By: Relevance
“…After filtering the sequence data for TRAV26-1 paired with the canonical CDR3β found in DQ2.5:DQ2.5-glia-α2-reactive T cells only, we found that TRBV7-3 was in fact used, but 5 times less frequently than TRBV7-2 (Table 2). Interestingly, this difference corresponds well with the relative expression of TRBV7-2 and TRBV7-3 as reported in the naive repertoire (22,23). We also looked for TRAV26-2 and found it in 6 clonotypes (of 536 clonotypes in the total pool).…”
Section: Generation Of α-Gliadin-specific T Cell Clones and Tcr Clonisupporting
confidence: 85%
See 1 more Smart Citation
“…After filtering the sequence data for TRAV26-1 paired with the canonical CDR3β found in DQ2.5:DQ2.5-glia-α2-reactive T cells only, we found that TRBV7-3 was in fact used, but 5 times less frequently than TRBV7-2 (Table 2). Interestingly, this difference corresponds well with the relative expression of TRBV7-2 and TRBV7-3 as reported in the naive repertoire (22,23). We also looked for TRAV26-2 and found it in 6 clonotypes (of 536 clonotypes in the total pool).…”
Section: Generation Of α-Gliadin-specific T Cell Clones and Tcr Clonisupporting
confidence: 85%
“…We did indeed find TRBV7-3 to be present, and the TRAV26-1/TRBV7-3 T cells formed the canonical CDR3β. Furthermore, the difference in the representation of TRBV7-2 versus TRBV7-3 mirrored the abundance of these gene segments in the naive repertoire (22,23). Whether this is a general feature of antigen-expanded T cell populations remains unclear, but a previous study found that antigendriven expansion of CD4 + T cells was reflected by the frequency of naive progenitors (26).…”
Section: Discussionmentioning
confidence: 97%
“…In principle, such a model could be combined within our framework to yield refined sharing predictions. While the parameters of the generation process are largely invariant across individuals,29 selection is expected to be individual‐dependent and heritable due to the diversity of HLA types in the population 59. The large variability in the V and J genes selection pressures inferred previously20 is consistent with this notion, but in the same work some amino acid features of selection were found to be universal.…”
Section: Discussionmentioning
confidence: 61%
“…We showed that repertoires constructed by I g R e C from various non-barcoded Rep-seq datasets (e.g., datasets with high expression level (59)) are well-suited for various downstream applications such as clonal analysis or immunoproteogenomics. On the other hand, barcoded Rep-seq datasets may still be needed for specialized studies aimed at accurate quantification and detection of low-abundance receptor sequences such as studies of naive and memory cells requiring extensive amplification as in studies of long-term immune response (60, 54). …”
Section: Discussionmentioning
confidence: 99%